South Africa’s Strategy for the Management of Derelict and Ownerless Mines - Coetzee, H; Nengobela, NR; Vorster, C; Sebake, D; Mudau, S (Mine Closure 2008: Proceedings of the Third International Seminar on Mine Closure, 2008)
South Africa’s long and rich mining history has left a legacy of approximately six thousand abandoned mines in the country. Many of these could be legally classified as “derelict and ownerless”, and will require intervention by the state in order to address safety, health and environmental legacies. In order to address these, the Department of Minerals and Energy, in partnership with the Council for Geoscience, has developed a strategy for the management of these legacies. The initial phase of the development and implementation of this strategy is detailed in this paper and comprises three main components: the compilation and verification of a database of abandoned mines, the ranking of these mines in terms of their priority for rehabilitation and a proposal for the management of these sites, which amongst other things includes a rehabilitation plan, based on the results of the initial phase of the ranking exercise.